Γ-Mangostin, a xanthone from mangosteen, attenuates oxidative injury in liver via NRF2 and SIRT1 induction. (January 2018) - Wang, Anqi; Li, Dan; Wang, Shengpeng; Zhou, Fayang; Li, Peng; Wang, Yitao; Lin, Ligen
Highlights: A xanthone, γ-mangostin, was obtained from the pericarps of Garcinia mangostana L. γ-Mangostin protects hepatocytes from oxidative injury in vitro and in vivo . γ-Mangostin causes nuclear translocation of NRF2 to enhance antioxidant capacity. γ-Mangostin increases the expression and deacetylation activity of SIRT1. γ-Mangostin activates PGC-1α to enhance mitochondrial function. Abstract: γ-Mangostin (γ-man), an active compound from Garcinia mangostana L., has been discovered as a hepatoprotective agent against oxidative injury. However, the underlying mechanisms remained unclear. The current study showed that γ-man stimulated the nuclear translocation of nuclear factor erythroid 2-related factor 2 (NRF2) to enhance antioxidant capacity under oxidative stress, which was partially reversed by treatment of the NRF2 inhibitor, all-trans-retinoic acid. Moreover, γ-man increased the expression and activity of SIRT1 (silent mating type information regulation 2 homolog 1), which facilitated the deacetylation of peroxisome proliferator-activated receptor γ coactivator 1α to improve the mitochondrial function in L02 cells. The protective effect of γ-man was partially blocked by treatment of the SIRT1 inhibitor tenovin-1 or SIRT1 knockdown. In vivo studies showed γ-man protected mice from carbon tetrachloride-induced acute liver injury, through up-regulation of NRF2 and SIRT1. Thus, γ-man might be a candidate to protect liver from acute oxidative injury.